Memory T Cell Subpopulations as Early Predictors of Remission to Vedolizumab in Ulcerative Colitis - Gonzalez-Vivo, Maria; Lund Tiirikainen, Minna K.; Andreu, Montserrat; Fernandez-Clotet, Agnes; López-García, Alicia; Murciano Gonzalo, Francisca; Abril Rodriguez, Lourdes; de Jesús-Gil, Carmen; Ruiz-Romeu, Ester; Sans-de San Nicolàs, Lídia; Santamaria-Babí, Lluis F.; Márquez-Mosquera, Lucía (Frontiers in Medicine, 2022)
Background. Vedolizumab is a humanized monoclonal antibody targeting the α4β7 integrin used for the treatment of ulcerative colitis. Few biomarkers related to vedolizumab response have been identified. The aim of this work was to assess whether baseline circulating CD4+ and CD8+ memory T-lymphocyte subpopulations could help to identify patients with response to vedolizumab treatment in ulcerative colitis. Methods. Prospective pilot study in 15 patients with active ulcerative colitis and previous failure to anti-TNF starting vedolizumab treatment. Peripheral blood samples were obtained before the first dose of vedolizumab and atweek 6 and 14 of treatment. Clinical remission was defined as a Mayo Clinic partial score of <2 points without any concomitant dose of steroids. Biochemical remission or endoscopic improvement was defined as fecal calprotectin <250 mcg/g or Mayo endoscopic subscore <1. Results. At week 14, nine patients achieved clinical remission and eight patients achieved biochemical remission or endoscopic improvement. Patients in clinical remission presented higher baseline CD8 α4β7+memory T cells concentration when compared with patients with no remission. In addition, patients with biochemical remission or endoscopic improvement at week 14 presented higher baseline concentration of CD8 α4β7+memory T cells. No differences were identified according to flare severity, extent of disease or type of antiTNF-α failure. There were no significant differences regarding changes in T cell subsets during vedolizumab induction. Conclusion. CD8+ α4β7+ memory T cells before starting vedolizumab therapy could be an early predictor of remission and therefore help to select a subset of responders.